Design of Clean Water Piping in Cibeureum, Cimahi, West Java (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Piping planning needs to be done to simplify the water distribution process. Starting from the inlet to the oulet. The piping design process is carried out according to field conditions. The implementation is carried out in areas in the area of ​​KP2A (Water User and User Groups), RW 14, Cibeurum Village, South Cimahi. The existing condition is that there are 2 water source pipes (1.8 liters / second) from artesian directly to Toren without any filtering process, there is a water reservoir measuring 1.6m x 2m x 2.2m x 3 tubs. This water capacity to distribute 180 families. The planning of the piping starts from the pipe coming out of the water source, entering the toren, until the backwash dirty water disposal pipe is discharged out, as well as adjusting to the dimensions of the existing water tank. The existing water tanks remain and are not damaged. Some of the important components needed in this installation include 4 toren, PVC pipe, watermur, valve, reducer, elbow, all of which are located around the site. The piping installation on 4 toren with the same water source is the installation mechanism of the toren inlet pipe, toren backwash oulet pipe and toren backwash inlet pipe, so that when the backwash process occurs, replacement of filter media, and repair of toren, it will not affect the another toren.The advantage of this piping design is that the cleaning process on one toren can be done without disturbing the other toren. Also during the cleaning / maintenance process on one toren it can be done without disturbing the other toren.